Catalytic combustion of soot with a O2/NO mixture. KNO3/ZrO2 - Carrascull, Alfredo Lazaro (2003)
Catalysts containing 0.25–20% KNO3 supported on ZrO2 have been studied for diesel soot combustion. The addition of KNO3 to ZrO2 support enhances its activity due to the increased contact between soot and catalyst and also because the KNO3 acts as catalyst. The combustion temperature has been measured for “loose” and “tight” contact, between soot and catalyst, and the difference was 10 K for KNO3(20)/ZrO2 catalyst. This finding is very important because under practical conditions the contact between soot and catalyst is poor and this contact resembles the contact denoted as “loose contact”.